TANTRA SEBAGAI JALAN MENGAKTUALISASIKAN DIRI DALAM MENCAPAI TUHAN DI ERA DIGITAL - I Gusti Made Widya Sena (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The world of ideas is a complex world full of twist and turns. Various thoughts that arise in one`s head are the result of stimulation of the five senses with the surrounding environment. This shows that the functions of the five senses cannot be ruled out in managing the mind into practical actions that can be fulfilled in daily life. The desire to achieve mind awareness about a strong desire to change the way of thinking and thinking becomes more natural in achieving the desired goals. The objectives that must be completed are becoming increasingly complicated in this digital era, because in an increasing sophisticated era with the development of information technology that is causing increasing needs. These needs require: phsyological needs, security and comfort needs, social needs, needs for love and appreciation and self actualization needs. The various needs above will increase in accordance with the desire to have a better life.This article adopts the author to discuss the causes, process and implications of self-actualization in reaching God at the digital era. This paper uses a data collection method consisting of observations and documents. The analysis technique used is qualitative and presented descriptively. The result of this this paper are obtained when self actualization is due: (1) longing, (2) dreams, (3) self surrender-self acceptance. The process of self actualization is carried out through the path of tantra yoga so as to obtain responsible person, ready to change, having storong motives, using positive experiences and always developing themselves.